Sadr ad-din Konyavi and his contemporaries - Гульшени, С. Дж. (Journal of Oriental Studies, 2017)
The 13 th century considered as the hightest point and most important period of Islamic Mysticizm. Thus, the popular, even sufis lived and wrote their works during this period. The short information about the life and works of famous Sufis of that period – the main representatives of the environment Sadr aed –Din Qunawi grew up in is given in this article. In works of Konyavi along with influence Ibn Arabi, it is noticeable as well Nassir Tusi’s influence, the great scientist, the astronomer, the mathematician. It should be noted also that almost best-known sufi lived in the Islamic world in the 13th century, and SADR hell dyne Konyavi has had the luck to talk, and be on friendly terms with many of them or with their followers and pupils.